Effect of Dry Extract of Gerania Holmova on Hypoxia in Experimental Animals - Z.T.Fayziyeva; Z.A.Khakimova; Z.T.Pazilbekova (Genius Journals, 2022)
Antihypoxants are increasingly prescribed as part of combined pharmacotherapy for various diseases accompanied by conditions of hypoxia and ischemia. If we outline the range of main indications for the use of antihypoxants, then we can identify such significant areas of their use as neuroprotection, cardioprotection, angiprotection, hepatoprotection, gastroprotection [4]. In practical medicine, antihypoxants with different mechanisms of action are used
Keywords: Antihypoxants; mechanisms; neuroprotection; hepatoprotection